2021
DOI: 10.1007/s40265-021-01487-0
|View full text |Cite|
|
Sign up to set email alerts
|

Nintedanib: A Review in Fibrotic Interstitial Lung Diseases

Abstract: Progressive fibrosing interstitial lung diseases (ILDs) involve similar pathophysiological processes, indicating the potential for common approaches to treatment. Nintedanib (Ofev ® ), an intracellular tyrosine kinase inhibitor (TKI) with antifibrotic properties, was one of the first drugs approved for use in idiopathic pulmonary fibrosis (IPF) and has more recently been approved for use in other chronic fibrosing ILDs with a progressive phenotype and systemic sclerosis-associated ILD (SSc-ILD). In multination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 85 publications
2
59
0
5
Order By: Relevance
“…Of note, nintedanib was also shown to ameliorate experimental PAH via inhibition of EndoMT and pulmonary arterial VSMC proliferation, suggesting that this molecule might be used as a therapeutic agent for PAH by preventing fibroproliferative vascular remodeling [ 127 ]. Clinically, treatment with nintedanib was able to reduce the decline in forced vital capacity in SSc patients suffering from ILD [ 128 , 129 , 130 ], even if when considering patients with a background therapy with mycophenolate, such a decline did not significantly differ from placebo-treated patients [ 131 ]. In addition, given its relevant side effects, the effective safety and efficacy of nintedanib for SSc treatment has yet to be fully investigated [ 43 , 117 ].…”
Section: Main Molecular Pathways Driving Myofibroblast Differentiation From Vascular Wall Residing Cells In Systemic Sclerosis and Relatementioning
confidence: 99%
“…Of note, nintedanib was also shown to ameliorate experimental PAH via inhibition of EndoMT and pulmonary arterial VSMC proliferation, suggesting that this molecule might be used as a therapeutic agent for PAH by preventing fibroproliferative vascular remodeling [ 127 ]. Clinically, treatment with nintedanib was able to reduce the decline in forced vital capacity in SSc patients suffering from ILD [ 128 , 129 , 130 ], even if when considering patients with a background therapy with mycophenolate, such a decline did not significantly differ from placebo-treated patients [ 131 ]. In addition, given its relevant side effects, the effective safety and efficacy of nintedanib for SSc treatment has yet to be fully investigated [ 43 , 117 ].…”
Section: Main Molecular Pathways Driving Myofibroblast Differentiation From Vascular Wall Residing Cells In Systemic Sclerosis and Relatementioning
confidence: 99%
“…In multinational phase III trials, including open-label extensions, and real-world experience, the drug has demonstrated clinical benefit persisting over long-term treatment, with a manageable tolerability profile [ 1 ]. Nintedanib significantly reduced the annual rate of decline in forced vital capacity in patients with IPF and severe gas exchange impairment as well as in subjects with milder disease.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from diarrhea, bleeding, and arterial thromboembolism, drug-induced liver injury (DILI), albeit uncommon, emerged as an adverse event (AE) of special interest [ 1 ]. Imbalances were noted in pivotal clinical trials: elevations in alanine aminotransferase, aspartate aminotransferase, or both to levels ≥ 3 times the upper limit of the normal range (ULN) were observed in 13.0% of the subjects with progressive fibrosing ILDs treated with nintedanib (vs. 1.8% in the placebo group), with only one patient in each group meeting criteria for Hy’s law [ 3 ]; the respective proportions were 4.9% vs. 0.7% in SSc-ILD [ 4 ], 4.9% vs. 0.5% in INPULSIS-1, and 5.2% vs. 0.9% in INPULSIS-2 trials [ 5 ], with no individuals meeting criteria for Hy’s law in IPF.…”
Section: Introductionmentioning
confidence: 99%
“…These effects on receptor tyrosine kinases lead to decreased fibroblast activity. 5,64,65 INPULSIS phase 3 trials I and II showed a significant decrease in the rate of FVC deterioration in IPF patients although the death rate remained the same. 66 The side effects, primarily diarrhea and nausea, are manageable with medication, but hepatotoxicity may occur in rare cases and the drug is not recommended for those with severe liver disease.…”
Section: Current Pharmacologic Treatmentsmentioning
confidence: 98%